Testing the Performance of the Video Camera to Monitor the Vertical Movements of the Structure via a Specially Designed Steel Beam Apparatus - Eren, Mehmet; Hosbas, Ramazan Guersel (SCIENDO, 2023)
This article focuses on a specially designed steel beam testing apparatus to determine the dynamics of the structure using data obtained from different sensor systems. The analysis of these different sensor systems is performed by processing data recorded by the Global Navigation Satellite System (GNSS), vision based measurement (video camera), and accelerometer surveys. To perform this analysis, the accelerometer and GNSS receiver are installed at the steel beam's mid-span position. The high-contrast artificial target attached to the accelerometer is recorded by a video camera to monitor the structural dynamics. Steel beam experiments show that it is compatible with the accelerometer, which is predicted as a reference sensor in detecting motion with an amplitude of 10 mm and above in the vertical direction with GNSS and determining the structural frequency by spectral analysis. On the other hand, we concluded that the video camera can be used to determine the structural dynamics in SHM because its results were compatible with the reference data even if the amplitude was too small.
Keywords: SHM; vision-based measurement; vertical displacement; kinematic PPP; GNSS; frequency; POINT POSITIONING PPP; GPS; BRIDGE; OSCILLATIONS; VISION; Instruments & Instrumentation